Análise da estrutura produtiva da microrregião de Frederico Westphalen (2005 – 2015) - Wiechork, Sandro (2017)
This work intended to analyze if there was evolution and dynamics of the economic basis of Frederico Westphalen microregion, in Rio Grande do Sul, considered economically poor, if it’s compared to the other regions of this state. Douglass North's theoretical contribution about economic basis theory was used to explain the development of the region with the export of its products to other regions or countries, associating the commercialization of its goods with economic development and separating the activities in basic and not basic ones. So, the research showed in what activities the microregion is specialized and in what cities, making a comparative analysis among 2005, 2010 and 2015. In order to analyze the specialization or diversification of the activities, we used the employment multiplier, locational quotient (LQ) and the specialization coefficient (SC) for the microregion in relation to the state. Additionally, the last one was calculated for the cities in relation to the microregion to identify which cities lead the microregion to have (or not) the same trend of state specialization. The employment multiplier, used to identify the elements of the export basis, presented higher value than the unit for all years, relating the employment with the basic activities. The SC pointed six sectors that can be considered as export basis: non-metallic mineral production, textile industry, food and beverages, retail business, financial institution and public administration. Although agriculture is still very present in the region, it isn’t a basic export activity; but North characterizes it as a basic activity naturally. The SC used to analyze the productive structure of the cities registered similar values for most of them. However, six of them stand out with a specific structure: Cristal do Sul, Dois Irmãos das Missões, Gramado dos Loureiros, Novo Tiradentes, Novo Xingu and Rio dos Índios. Therefore, the study did not indicate rates that demonstrate the triggering of the economic basis of the cities in the microregion, pointing a lack of value aggregated to that economic basis, so that it can be attractive and can transform itself.